Culture of Selected Microalgae in Rubber and Palm Oil Mill Effluents and their Use in the Production of Enriched Rotifers - Habib, M. Ahsan (1998)
Three freshwater microalgae Chlorella vulgaris, Selellastrum gracile and Ankistrodesmus convolutlls showed high growth performances in terms of specific growth rate (SGR) of cell and chlorophyll a, total carotene and observed yield when grown in inorganic media with sodium acetate. Total protein of S. gracile was higher than A. convolutus followed by C. vulgaris, whereas reverse trend was observed in the case of total lipid. Among 11 essential amino acids (EAAs), phenylalanine, leucine and lysine were found to be higher in C. vulgaris, S. gracile and A. convolutus than other EAAS. All the evaluated polyunsaturated fatty acids (PUFAs) of CIS, C20 and C22 were higher in C. vulgaris grown in Bold Basal Medium with sodium (Na) acetate (BBMAC) and Modified Medium with Na acetate (MMAC) than cultured in other media. In addition, S. gracile and A. convolutus grown in BBMAC and MMAC contained significantly (p<0.05) higher amount of PUFAs except linolenic acid ( 18:3n-3 ) and eicosatrienoic acid (20: 3n-6) than cultured in other media. All together 26 essential minerals were detected and 22 essential minerals were quantified where total bioaccumulated minerals was below the optimum level and significantly (p <0.01) correlated with these minerals available in media.